Pest categorisation of Hirschmanniella spp. - Jeger, Michael (EFSA J, 2018)
The Panel on Plant Health performed a pest categorisation of nematodes belonging to the genus Hirschmanniella (Nematoda: Pratylenchidae). Twenty‐nine species in this genus have been considered of which five species are present in the EU (Hirschmanniella behningi, Hirschmanniella gracilis, Hirschmanniella halophila, Hirschmanniella loofi and Hirschmanniella zostericola). The whole genus except H. gracilis is regulated by Council Directive 2000/29/EC (Annex IAI). Hirschmanniella species are root endoparasites uniquely adapted to aquatic environments. Most species are reported from tropical regions. Monocotyledons including aquatic plants are main hosts and some Hirschmanniella species are important pests of rice. Plants for planting are potential pathways for entry. Hirschmanniella species are frequently intercepted on imported aquarium plants. Measures are available to avoid entry. Environmental conditions in greenhouses and potentially in rice production areas of the EU are suitable for establishment. The nematode may be spread with irrigation, tools or plants for planting. Hirschmanniella species were categorised into four groups. The first group includes species reported as pests of crop plants; those satisfy all the criteria that are within the remit of EFSA to assess to be regarded as Union quarantine pests. The second group includes species that are not reported to cause economic damage to crop plants; those species do not satisfy all the criteria to be regarded as Union quarantine pests. Uncertainty exists whether species in this group can cause damage once introduced into the EU. The third group includes species that are known to be present in the EU and do not cause damage; they do not satisfy the criteria to be regarded as Union quarantine pests or regulated non‐quarantine pests. The fourth group consists of H. gracilis only. This worldwide occurring species is present in the EU where it does not cause economic damage. It does not satisfy all the criteria to be regarded as a Union quarantine pest.